Fungi Indirectly Affect Plant Root Architecture by Modulating Soil Volatile Organic Compounds - Schenkel, Denis; Maciá-Vicente, Jose G.; Bissell, Alexander; Splivallo, Richard (Frontiers in Microbiology, 2018)
The plant-growth modulating effect of microbial volatile organic compounds (VOC) has been demonstrated repeatedly. This has most often been performed by exposing plants to VOC released by microbes grown on nutrient rich media. Here, we used soil instead to grow fungi of the Fusarium genus and investigate how VOCs emitted by this system influenced the development of Arabidopsis plants. The volatile profiles of Fusarium strains grown in soil and malt extract were also compared. Our results demonstrate that distinct volatile signatures can be attributed to different Fusarium genetic clades but also highlight a major influence of the growth medium on volatile emission. Furthermore, all soil-grown Fusarium isolates increased primary root length in Arabidopsis by decreasing VOC concentrations in soil. This result represents a major paradigm shift in plant-microbe interactions since growth modulating effects have been attributed so far to the emission and not the consumption of volatile signals.